Study of Evolutionary Algorithms for Multi-objective Optimization - Gaikwad, Rama; Lakshmanan, Ramanathan (SN computer science, 2022)
There are two prominent principles of any information retrieval system precision and analysis. Precision is the proportion of correct documents retrieved by the information retrieval system to the total number of archives retrieved in the perspective of a client's inquiry. Analysis includes the way these documents are expected to be retrieved by the client. Predicting the documents that the user might need in the upcoming time is also crucial. Having the list of multiple objectives in the user query and getting the optimum result adhering to the objectives are important these days where we can make use of evolutionary algorithms which provides set of solutions to the problem. We present here in this paper study of useful multi-objective optimization algorithms, recent developments in multi-objective evolutionary algorithms, and literature which have used these algorithms. Further, we discussed our proposed system where we will make use of the knowledge gained from this examination.